A Systematic Review of Aminaphtone from Pathophysiology to Clinical Applications: Focus on New Rheumatological Acquisitions - Emanuele Gotelli; Stefano Soldano; Elvis Hysa; Greta Pacini; Carmen Pizzorni; Sabrina Paolino; Maurizio Cutolo; Alberto Sulli (MDPI AG, 2023)
Aminaphtone is a chemical drug that has been used for more than thirty years to treat a variety of vascular disorders, with good clinical results and a satisfying safety profile. In the last two decades, multiple clinical studies have reported the efficacy of the drug in different clinical scenarios of altered microvascular reactivity, describing the downregulation of adhesion molecules (i.e., VCAM, ICAM, Selectins), vasoconstrictor peptides (i.e., Endothelin-1), and pro-inflammatory cytokine expression (i.e., IL-6, IL-10, VEGF, TGF-beta) by Aminaphtone. In this review, we summarize the current knowledge concerning Aminaphtone, with particular attention to rheumatological conditions in which microvascular disfunction plays a pivotal role, such as Raynaud's phenomenon and systemic sclerosis. These latter conditions may represent a promising field of application for Aminaphtone, due to the growing pre-clinical, clinical, and instrumental reports of efficacy. However, randomized, double-blind, placebo-controlled clinical trials are lacking and are desirable.